Perlindungan Hukum Terhadap Pekerja PKWTT (Perjanjian Kerja Waktu Tidak Tertentu) yang Tidak Mendapatkan Upah - Auliadi Achmad Davin; Rasji Rasji (Dinasti Review Publisher, 2024)
Issues related to employment seem to have become an issue that is always hotly discussed, especially related to the widespread phenomenon of unilateral termination of employment by employers who then invited the author to discuss the decision 76/Pdt.Sus-PHI/2023/PN Jkt Pst, where PKWTT workers did not receive their wages at all from September 2016 to February 2021 and were terminated without official information. This issue is interesting to discuss, especially regarding the form of protection for PKWTT who experience Termination of Employment Relations and reflecting this with the judge's consideration of the a quo decision in terms of the Employment Law which in its development was revised with the Job Creation Law and gave birth to implementing regulations PP Number 35 of 2021 and PP Number 36 of 2021. In this research, the author uses normative juridical research methods using literature studies and a legal approach. The research results show that PKWTT who experience layoffs are entitled to severance pay, UPMK, and separation pay as well as other benefits required by the government such as THR. PKWTT who feel aggrieved also have the right to submit non-litigation legal remedies as a priority for settlement, then if this is not achieved, they can submit litigation legal remedies. In essence, the judge's considerations in handing down the a quo decision were appropriate in referring to the formulation of severance pay calculations in accordance with applicable regulations. The government needs to aggressively continue to carry out outreach regarding labor regulations and routinely open communication spaces with workers and employers to then adjust existing labor regulations.